2014
DOI: 10.1039/c4tb00690a
|View full text |Cite
|
Sign up to set email alerts
|

A novel zwitterionic bioceramic with dual antibacterial capability

Abstract: A novel zwitterionic bioceramic is developed, capable of lowering the relative bacterial adhesion from 100% to below 0.1%, as derived from in vitro assays using S. aureus. This matrix can release antibiotics over a long time and provides new insights in the treatment of bone implant infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…[15][16][17][18][19][20] These antibacterial surfaces can be constructed through two different methods: anti-adhesive coating to resist bacterial adhesion and bactericidal surface to kill contacting bacteria. Many kinds of anti-adhesive coatings have been designed and prepared to reduce bacterial adhesion.…”
Section: Wang Et Almentioning
confidence: 99%
“…[15][16][17][18][19][20] These antibacterial surfaces can be constructed through two different methods: anti-adhesive coating to resist bacterial adhesion and bactericidal surface to kill contacting bacteria. Many kinds of anti-adhesive coatings have been designed and prepared to reduce bacterial adhesion.…”
Section: Wang Et Almentioning
confidence: 99%
“…-NH 3  /NH 2 and COO Θ /COOH pairs), which allows determining the zwitterionic nature of a bioceramic [17,24,31,32]. Figure 3 shows FTIR spectra corresponding to pure silica SBA-15 and zwitter-SBA15 materials, chosen as representative examples (structure 4, Figure 2) [31].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…The results demonstrated that zwitterionic SBA-15 exhibited good biocompatibility with Saos-2 osteoblasts adhering, proliferating and maintaining its morphological and functional characteristics [45] . Recently, the design and synthesis of a new zwitterionic SBA-15 type bioceramic with dual antibacterial ability has been reported [46] . Its non-fouling capability was derived from the inherent zwitterionic nature of the surface, while the bactericidal capability resulted from its capability to host antibiotics into the mesopores.…”
Section: Zwitterionization Of Biomaterialsmentioning
confidence: 99%